Nitrogen and sulfur interaction on nutrient use efficiencies and diagnostic tools in maize - Carciochi, Walter Daniel; Salvagiotti, Fernando; Pagani, Agustin; Reussi Calvo, Nahuel Ignacio; Eyherabide, Mercedes; Sainz Rozas, Hernan Rene; Ciampitti, Ignacio A. (Elsevier, 2020)
Nitrogen (N) and sulfur (S) critical dilution curves and the N:S stoichiometry are useful tools for evaluating nutrient status in maize (Zea mays L.). Nutrient supply for both N and S impact plant nutrient uptake, consequently influencing the overall performance of fertilization diagnostic tools. Interaction between these nutrients has not been studied relative to their nutrient use efficiencies (NUE and SUE), agronomic efficiencies (NAE and SAE), and components of these. The aim of this study was to analyze the effect of N and S fertilization on: i) N and S uptake (NU and SU) dynamics, ii) N and S dilution curves, iii) N:S stoichiometry, and iv) NUE, SUE, NAE, SAE, and their components in maize. Five maize field trials were conducted evaluating the effect of N and S fertilization with two levels for each nutrient (unfertilized and fertilized). Maize shoot biomass and its N and S concentrations were measured from six-leaf to physiological maturity. The main outcomes of this study were: i) averaged across sites, N fertilization increased yield by 41% and S fertilization by 10%; ii) SU was delayed relative to NU; iii) S fertilization increased shoot S concentration when N was not limiting; iv) N dilution curve was not affected by S supply; v) N:S ratio decreased with increasing shoot biomass and varied with N and S supply; vi) N fertilization improved SUE and SAE via greater S recovery, with a similar S fertilization effect on NUE and NAE. This study demonstrated that both the critical S dilution curve and N:S stoichiometry are useful tools to characterize S status when N is not deficient. Simultaneous N and S management is critical for increasing their use efficiencies, improving crop productivity, and reducing environmental footprint.